HIV-Related Non-Hodgkin’s Lymphoma in Calgary - Paul L Beck; M John Gill; Walter B Blahey; Lloyd R Sutherland (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the incidence of human immunodeficiency virus (HIV) associated non-Hodgkin’s lymphoma (NHL) in a cohort of patients from a distinct geographic region (southern Alberta). The type and location of NHL as well as how it affected the survival of these patients was examined.